The Effect of Foliar Application of Azolla Liquid Organic Fertilizer on Growth and Yield of Rice in Swampy Soil - Rohayani, Mei; Widodo; Masdar; Gusmara, Herry (TERRA : Journal of Land Restoration, 2024)
Rice cultivation faces challenges due to limited land availability despite increasing demand. Utilizing swamp land for cultivation presents an alternative, albeit hindered by difficult-to-control water conditions and less effective fertilizer spread. To ensure optimal nutrient supply, foliar application of Azolla liquid organic fertilizer (LOF) is explored. This study investigates the ideal concentration and frequency of Azolla LOF application for rice growth and yield. Employing a split plot design, the main plot assesses LOF concentration (3%, 6%, 9%, 12%), while the subplot evaluates application frequency (1, 2, 3 times). Results indicate that a 9% LOF concentration yields the highest tiller count (17.99), longest panicle (25.788 cm), highest grain count per panicle (158.2978), heaviest grain weight per hill (45.878 g), and highest grain weight per plot (3457.52 g). However, the fastest flowering period (54 DAP) occurs with a 12% LOF concentration. Applying Azolla LOF three times achieves the earliest flowering (55.25 DAP), while two applications yield the longest panicle (25.03 cm). Notably, no interaction is observed between LOF concentration and application frequency on rice growth and yield. These findings provide insights into optimizing Azolla LOF application for enhanced rice cultivation in swamp lands.